Assessing the Impact of Socio-Technical Dependencies on Software Defect (Sains Humanika, 2017)
One of the measures used to fit or align social and technical dependencies is known as Socio-Technical Congruence (STC). However, STC is a new and vastly unexplored area. To our best knowledge, there has been limited research done on the use of STC in software engineering projects. Hence, this provides an opportunity to extend the body of knowledge by investigating the impact of STC on other measures such as software quality. This paper outlines the motivation behind this said research, the methodology and expected findings of this research. This research aims to provide further information about the domain of STC in software engineering field, specifically its relationship with software quality. The expected result of this research is a higher level of congruence in a development project can yield a higher quality project.Â
Keywords: Socio-technical congruence; actual coordination; coordination requirements; software engineering projects; software quality